2004
DOI: 10.1079/bjn20031088
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fat replacement by inulin or lupin-kernel fibre on sausage patty acceptability, post-meal perceptions of satiety and food intake in men

Abstract: The present study examined whether replacing fat with inulin or lupin-kernel fibre influenced palatability, perceptions of satiety, and food intake in thirty-three healthy men (mean age 52 years, BMI 27·4 kg/m 2 ), using a within-subject design. On separate occasions, after fasting overnight, the participants consumed a breakfast consisting primarily of either a full-fat sausage patty (FFP) or a reduced-fat patty containing inulin (INP) or lupin-kernel fibre (LKP). Breakfast variants were alike in mass, protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
94
1
4

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(100 citation statements)
references
References 37 publications
0
94
1
4
Order By: Relevance
“…More specifically, a postprandial study has demonstrated the highly satiating effects of LKFibre, suggesting that it may have potential in obesity-control diets (Archer et al, 2004). The results of the present study do not support these earlier findings.…”
Section: Discussioncontrasting
confidence: 99%
“…More specifically, a postprandial study has demonstrated the highly satiating effects of LKFibre, suggesting that it may have potential in obesity-control diets (Archer et al, 2004). The results of the present study do not support these earlier findings.…”
Section: Discussioncontrasting
confidence: 99%
“…Satiety ratings were not significantly altered (56) . However, control and inulin-containing sausage patties were not matched for energy in this study.…”
Section: Colonic Delivery Of Scfa To Investigate Appetite Effects Fomentioning
confidence: 76%
“…18 interpretation difficult (Archer, et al, 2004). In our study the control was energy and macronutrient 389 matched to the investigative products.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 84%
“…In common with our findings, a previous trial in 22 unrestrained females 382 found acute ingestion of 10 g long-chain inulin within a chocolate crisp bar did not alter qualitative 383 or quantitative appetite measures in comparison to a control bar (Karalus, et al, 2012). By contrast 384 24 g long-chain inulin used as a fat-replacer in sausage patties significantly reduced 24-h EI in 385 comparison to a full fat patty in an acute meal challenge in healthy participants (n=33), although 386 rated satiety was not altered, and ad libitum EI was not investigated (Archer, et al, 2004). However,M A N U S C R I P T…”
Section: Taste Ratings 324mentioning
confidence: 89%